FOLKLORE TRADITIONS IN EPIC “LISONUT-TAYR” (Scientific journal of the Fergana State University, 2023)
This article analyzes the phrases, proverbs, legends and myths related to folklore in Alisher Navoi’s epic “Lisonut-tayr”. The content of the poetic verses quoted in the epic is explained. The national style of figurative imagery is based on the tradition of oriental literature